(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Dengue fever has become a major public health concern in recent years. The number of deaths caused by dengue is increasing over the years thus putting it in an alarming state. Public should be informed about the latest dengue cases around them. Most of them have to access various source of information to get this updates. M-Dengue, a web-based system has been proposed as a location-based platform for monitoring and reporting dengue cases, which allows information sharing in real time. It also includes dashboard that represent the data and act as a tool for analyzing, visualizing, classifying and geo-referencing dengue reports. The dashboard will helps the health staff to monitor this disease and make quick decisions. The system is proposed to benefit the community and to improve their health as well as the health of those around them. It is also aimed to engage the public as participants in the public health process as they could issue reports and share information regarding this threatening disease. The system is developed for the health staff and general public. Users are expected to be able to monitor dengue disease and gain the latest information regarding dengue cases in the country.